Instructors' Perceptions of the Use of Learning Analytics for Data-Driven Decision Making - Arnon Hershkovitz; G. Alex Ambrose; Tal Soffer (MDPI AG, 2024)
In recent years, much effort has been put into developing dedicated dashboards for instructors, in which data about students' activity are presented. However, in many cases, such endeavors take a top-down approach and do not involve instructors in the design process. In this paper, we present a study of instructors and teaching assistants in a research university in Israel (N = 253) who responded to an online questionnaire regarding their perceptions of data on students' activity on course websites. Specifically, they were asked about the types of data they were most interested in, the aspects of student learning that they would consider important, and the actions they would take upon viewing the data. Overall, we found that participants' scores were medium-high (2.5-3.5 on a 5-point Likert scale), with scores being higher for women compared with men and positively correlated with experience with Moodle. An overarching theme arises from our analyses of instructors' interests and intentions, which portrays their idea of teaching as somewhat traditional and instructor-centered; however, their declared actions make it clear that they are willing to make some desirable changes to the benefits of students. Finally, we found that instructors' perceptions of data use and data importance are positive predictors of taking action upon viewing student data.